Crack constitutive model to simulate the behavior of fiber reinforced concrete structures failing in punching - Gouveia, A. Ventura (2007)
For some structural applications, mainly with redundant supports, adding fibers to concrete can be an economic strategy, especially when shear brittle failure mode has a high risk of occurrence. In the present work, a crack constitutive model is proposed to simulate localized failure modes due to punching. The performance of the developed constitutive model was appraised by simulating the behavior observed in punching tests with lightweight panel prototypes of steel fiber reinforced self-compacting concrete (SFRSCC). The values of the parameters required by fracture mode I of the SFRSCC were obtained by inverse analysis.